Impact of Educational Interventional Programme Regarding Breast Feeding on the Level of Knowledge, Perception and Attitude of Post Natal Mothers - Nishanth Rajan; Kalaivani Anantharaaman; Priya Jose; Manikandan Mani; Peter Prasanth Kumar Kommu; Lalitha Krishnan (JCDR Research and Publications Pvt. Ltd., 2021)
Introduction: Nonpractice of breast feeding and noncompliance with immunisation are the two most important contributing factors of infant mortality which could be because of ignorance, illiteracy, social and cultural belief. Aim: To assess the level of knowledge, perception, and awareness among pregnant mothers after an educational intervention programme. Materials and Methods: A semi structured questionnaire was used for the pre & post-test experimental study among 145 mothers who delivered at a tertiary care center, Puducherry; during the study period of two months (November- December 2019). Those who were not willing to participate, who had postpartum complications were excluded from the study (15 mothers). Health education was imparted by one of the authors, in three stages. Stage I: Video demonstration of breast feeding for 10 minutes. Stage II: Focused group discussion for 10 minutes. Stage III: Mannequin demonstration for 10 minutes. Post-test was done on day three of life. Total of 37 questions in the form of yes/no, fill in the blanks and multiplechoice questions were used. Each question carried one mark. Wilcoxon signed rank test was used to describe the effectiveness of teaching by comparing pre-test - post-test score. The p-value of <0.05 was considered as statistically significant. Results: The median age of mothers was 26-30 years, around 62.7% were multiparous and about 50% had completed a basic undergraduate course. The post-test score of knowledge, attitude and perception were significantly higher than the pre-test scores (p-value =0.001). Conclusion: There is a significant improvement in the level of knowledge, perception and attitude regarding breast feeding after the educational intervention.